Elevated Systemic Levels of Eosinophil, Neutrophil, and Mast Cell Granular Proteins in Strongyloides Stercoralis Infection that Diminish following Treatment - Rajamanickam, Anuradha; Munisankar, Saravanan; Bhootra, Yukthi; Dolla, Chandra Kumar; Nutman, Thomas B.; Babu, Subash (Frontiers in Immunology, 2018)
Infection with the helminth parasite Strongyloides stercoralis (Ss) is commonly clinically asymptomatic that is often accompanied by peripheral eosinophilia. Granulocytes are activated during helminth infection and can act as immune effector cells. Plasma levels of eosinophil and neutrophil granular proteins provide an indirect measure of granulocyte degranulation and are markedly increased in many helminth-infected patients. In this study, we sought to examine the levels of eosinophil, neutrophil and mast cell activation-associated granule proteins in asymptomatic Ss infection and to understand their kinetics following anthelmintic therapy. To this end, we measured the plasma levels of eosinophil cationic protein, eosinophil derived neurotoxin, eosinophil peroxidase, eosinophil major basic protein, neutrophil elastase, myeloperoxidase, neutrophil proteinase-3, mast cell tryptase, leukotriene C4 and mast cell carboxypeptidase-A3 in individuals with asymptomatic Ss infection (INF) or without Ss infection (UN). We also measured the levels of all of these analytes in infected individuals following definitive treatment of Ss infection. We show that INF individuals have significantly higher plasma levels of eosinophil cationic protein, eosinophil derived neurotoxin, eosinophil peroxidase, eosinophil major basic protein, elastase, myeloperoxidase, mast cell tryptase, leukotriene C4 and carboxypeptidase-A3 compared to UN individuals. Following treatment of Ss infection, each of these granulocyte-associated proteins drop significantly. Our data suggest that eosinophil, neutrophil and mast cell activation may play a role in the response to Ss infection.